Anions for Near-Infrared Selective Organic Salt Photovoltaics. Issue 1 (December 2017) - Traverse, Christopher; Young, Margaret; Suddard-Bangsund, John; Patrick, Tyler; Bates, Matthew; Chen, Pei; Wingate, Brian; Lunt, Sophia; Anctil, Annick; Lunt, Richard
Abstract Organic molecular salts are an emerging and highly tunable class of materials for organic and transparent photovoltaics. In this work, we demonstrate novel phenyl borate and carborane-based anions paired with a near-infrared (NIR)-selective heptamethine cation. We further explore the effects of anion structures and functional groups on both device performance and physical properties. Changing the functional groups on the anion significantly alters the open circuit voltage and yields a clear dependence on electron withdrawing groups. Anion exchange is also shown to selectively alter the solubility and film surface energy of the resulting molecular salt, enabling the potential fabrication of solution-deposited cascade or multi-junction devices from orthogonal solvents. This study further expands the catalog and properties of organic salts for inexpensive, and stable NIR-selective molecular salt photovoltaics.